Іноземні інвестиції: визначення, сутність, класифікація - Ванькович, Л. Я.; Ковальчук, С. І. (Видавництво Національного університету "Львівська політехніка", 2008)
Уточнено поняття іноземних інвестицій, висвітлено думки різних авторів щодо питань іноземних інвестицій, відзначено суперечливі та проблемні моменти у них, подано власне тлумачення наведеного поняття, розкрито поняття іноземних інвестицій через їхню класифікацію за різними ознаками. The concept of foreign investments was specified in the article, opinions of different authors are reflected in relation to the questions of foreign investments, it is indicated on contradictory and problems moments for them, own interpretation of the resulted concept is given, the concept of foreign investments is exposed through their classification on different signs.